Organizational and methodical approaches to disclosure of income distribution in integrated reporting - Legenchyk S.F.; Polishchuk I.R. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The essence of the integrated reporting is described. Preconditions and problems when introducing the integrated reporting are presented. The information requests of integrated reporting users are described. The necessity of reflection of all types of capital, namely, natural, social, human and intellectual in the integrated reporting are revealed. The main advantages of compiling the integrated accounts for the enterprise are established: a broader perspective of consideration of the activity; the improvement of accounting policy as a result of integration of the principles of sustainable development into activity; increasing the trust of workers and consumers in the safety of technological processes and products for environment. For the wider introduction of the integrated reporting it is necessary to develop the methodological provision for accounting in accordance with the principles of sustainable development to ensure the reliability of the indices obtained; it is necessary to select the optimal list of indices that can meet the information needs of all users, in particular, investors, the state, auditors, society, creditors, consumers, employees, management personnel, academics, and the media. The main tasks and principles of compilation of the integrated reporting are presented. Orientation to the future, materiality, demand, integrity, reliability, completeness, periodicity, consistency, timeliness, interpretation, and comparability are suggested as the principles of integrated reporting. The issue of the necessity of conducting the external audit of the data verification of the integrity reporting is highlighted. The algorithm of profit distribution depending on the chosen strategy of enterprise development is proposed. When directing net profits for the development of production, the authors identify the following three strategies: insufficient upgrades, upgrades at the level of wear and the advanced renewal of non-current assets. It is proposed to choose the strategy for the extended renewal of non-current assets, which will increase the scope of activities and the net profit in the future.